You're invited – RSVP! The role of tailoring in incentivising people to delve into their pension situation - Milena Dinkova; Sanne K. Elling; Adriaan S. Kalwij; Leo R. Lentz (Utrecht University, Utrecht University School of Economics (U.S.E.), 2019)
This paper assesses whether offering tailored pension information based on age and gender is a way to get people interested in pension information. We conducted a randomised field experiment in which we sent email invitations to all employees of an insurance company to use an online tool, referred to as "the Pensioncheck", in order to learn more about their personal pension situation. This experimental set-up enabled us to answer the following research question: Does tailoring induce participants to perform the Pensioncheck? We found evidence that tailoring in the trigger phase can work in two opposite directions.
Keywords: 330; pension communication; pension information; tailoring; field experiment; financial decision making